Enhancement of 3D-Playfair algorithm using dual key. (19th March 2020) - Das, Arnab Kumar; Das, Nabanita
Playfair cipher is the one of the well known polyalphabetic cipher. In this paper, we present a new approach for secure transmission of a message by a modified version of the Playfair cipher combining with the ex-or operation and dual key. To develop this whole technique we used the three functions. One is generated the matrix and another two is encryption and decryption technique. The proposed extended 3D-Playfair cipher is working with 256 (4 × 8 × 8) characters, it selected 52 alphabets (upper case and lower case), ten numerals and 194 most commonly used special characters of ASCII character set. We use the 3D version of the Playfair cipher but we use the digraph concept. The restrictions of existing 2D-Playfair ciphers and 3D-Playfair cipher using 4 × 4 × 4 matrices, 6 × 4 × 4 matrices are overcome in the proposed work. The proposed algorithm can accumulate more characters than the existing 3D-Playfair ciphers.